Stabilization of air bubbles in oil by surfactant crystals: A route to produce air-in-oil foams and air-in-oil-in-water emulsions. (January 2015) - Brun, Mathieu; Delample, Mathieu; Harte, Etienne; Lecomte, Sophie; Leal-Calderon, Fernando
Abstract: The incorporation of air in vegetable oils is highly sought after as it allows reducing the total fat content, while providing a light and pleasant texture. To meet consumers' requirements, nonaqueous foams must remain kinetically stable for several months and must withstand large deformations and flows. In this paper, we describe the fabrication of air-in-oil foams of outstanding stability, both at rest and under flow, based on the use of crystallizable surfactants (mixture of mono- and diglycerides). The air volume fraction is close to 55%, irrespective of the surfactant concentration. The air bubbles are protected against coalescence and Ostwald ripening by a dense layer of crystals. Moreover, the firmness of the surfactant crystal network formed in the oil bulk is large enough to hinder buoyancy driven phenomena. Finally, we demonstrate that the oil foams can be dispersed in an aqueous phase containing hydrocolloids to form a novel type of material: air-in-oil-in-water (A/O/W) emulsions. Graphical abstract: Highlights: Mono and diglycerides crystals were used to stabilize air-in-water oil foams. Outstanding stability was obtained both at rest and under shear conditions. Stability was ensured by the network of crystals surrounding the bubbles. Air-in-oil-in-water emulsions (A/O/W) were successfully obtained. Our approach paves the way to the formulation of foods with low caloric content.